2020
DOI: 10.1071/es19029
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric rivers impacting mainland China and Australia: climatology and interannual variations

Abstract: In this study we have built two atmospheric river (AR) databases for mainland China and Australia using Japanese 55-year Reanalysis data with manual detections. By manually checking the magnitude, shape and orientation of vertically integrated vapour transport fields calculated from the reanalysis data and analysing its embedded synoptic patterns and other meteorological information, we detected 625 AR events over mainland China during 1986-2016 and 576 AR events over the Australian continent during 1977-2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 79 publications
4
51
0
Order By: Relevance
“…Firstly, during this period, a pair of ARs occurred in China and Australia and brought heavy precipitation in both regions. Secondly, as aforementioned in the Introduction section, results from Wu et al (2020) found that ARs in China tended to peak during the boreal summer season, whereas ARs in Australia tended to peak during the same time but in its cool season. Therefore, choosing the June 2016 boreal summer (austral winter) case further allowed us to investigate why ARs tend to share the same seasonality in Australia and China.…”
Section: Bifurcated Ars In the A-a Region: A Case Studymentioning
confidence: 77%
See 3 more Smart Citations
“…Firstly, during this period, a pair of ARs occurred in China and Australia and brought heavy precipitation in both regions. Secondly, as aforementioned in the Introduction section, results from Wu et al (2020) found that ARs in China tended to peak during the boreal summer season, whereas ARs in Australia tended to peak during the same time but in its cool season. Therefore, choosing the June 2016 boreal summer (austral winter) case further allowed us to investigate why ARs tend to share the same seasonality in Australia and China.…”
Section: Bifurcated Ars In the A-a Region: A Case Studymentioning
confidence: 77%
“…6c. It is also the peak season for the NCWB occurrence in the Australian region, as discussed in Ye et al (2020) and Wu et al (2020). From Fig.…”
Section: Connections Between the Wpsh And Subtropical High In The Ausmentioning
confidence: 80%
See 2 more Smart Citations
“…To address this issue, we need to examine the year-toyear variations. Although in the current collaborative AR project Wu et al (2020) produced a manual detected AR dataset, there is a lack of in-depth analysis of ARs and rainfall interannual variations in the Yangtze River region. We plan to develop our own AR automatic detection scheme that is more applicable in the East Asian region and then revise our results obtained in this study based on the resulting AR dataset.…”
Section: Summary and Discussionmentioning
confidence: 99%